Struktur Kepribadian Tokoh dalam Novel Segi Tiga Karya Sapardi Djoko Damono - Sahputri, Armita (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to describe the personality structure of the characters in the novel Segi Tiga using Sigmund Freud's psychoanalytic theory. The data source in this research is the novel Segi Tiga by Sapardi Djoko Damono. The focus of this research is on three characters by utilizing various dialogues and conflicts that occur. The results of research on the novel Segi Tiga by Sapardi Djoko Damono include the id which often dominates the character Suryo, making him a male character who often thinks irrationally in dealing with various problems. Meanwhile, the superego is the personality structure that dominates Noriko the most, making her a character who always thinks about the interests of other characters. Furthermore, the most dominant personality structure in Gendis is almost equal to the id, ego and superego. The id in Gendis acts based on instinct, while the ego always acts to satisfy the id in Gendis, giving rise to several problems, but the superego in Gendis is always the moral hand that guides Gendis to do good things.